Assistance to Administrative Units in Designing Standard Operating Procedures Based on Workload Analysis - al Qordhowi, Andrian Firdaus Yusuf (Universitas Pahlawan Tuanku Tambusai, 2024)
Administrative units often rely on formally standardized Standard Operating Procedures (SOPs) that are poorly aligned with actual workload conditions, resulting in procedural inefficiency and role ambiguity. This community service program aimed to support the development of workload-based SOPs to improve administrative efficiency, role clarity, and service effectiveness. A Participatory Action Research (PAR) approach was employed, encompassing diagnostic assessment, participatory workload analysis, collaborative SOP design, pilot implementation, and reflective evaluation. Data were collected through document analysis, participatory observation, interviews, workload measurement, and correlation analysis. The findings indicate that existing SOPs were structurally misaligned with workload distribution, leading to task overlap and uneven work allocation. The redesigned SOPs, grounded in workload indicators and developed through participatory processes, enhanced procedural clarity, reduced functional overlap, and strengthened staff ownership. This program demonstrates that participatory, workload-based SOP design is an effective strategy for evidence-based administrative reform and sustainable organizational learning.